EKSISTENSI TARI BARIS MATI DALAM UPACARA PIODALAN DI PURA DESA ADAT MANTRING TAMPAKSIRING KECAMATAN TAMPAKSIRING, GIANYAR - I Made Sudarsana; Komang Dedi Diana; A.A Dwi Dhirgantini (UNHI PRESS, 2021)
The existence of Baris Dance in Bali always gives a nuance that reflects local wisdom. In particular, the Baris Mati dance which is located in the Mantring Traditional Village and is also a guardian dance which is believed to be a dance to ward off reinforcements and Pamuput at the Piodalan Ceremony at the Desa Temple, the Mantring tradition of Tampaksiring, Gianyar. So based on this description, the problem of this research is focused on revealing and explaining the existence of the Baris Mati Dance in the piodalan ceremony at the Mantring Traditional Village Temple. With further problems can be formulated in the form of questions as follows: How is 1).existence, 2).form and function of the Baris Mati Dance at the Piodalan Ceremony of the Mantring Traditional Village Temple? This study was designed with a qualitative approach and then with a qualitative descriptive technique. Data analysis includes Data Reduction, Data Presentation, Conclusions, using Structural Functional theory, Aesthetic Theory, Religious Theory, Behavioristic Theory.The results of data analysis show the conclusion: Baris Mati Dance in the Mantring Traditional Village, Tampaksiring has four structures that are interrelated and support each other including: motion, composition, clothing, and accompaniment and have four functions, namely: Guardian Function, Religious Function, Social Function and Function Culture.